Mathematics Teachers and Digital Technology: A Quest for Teachers’ Professional Development in Indonesia - Wahyu, Kamirsyah; Ratnasari, Dwi; Mahfudy, Sofyan; Etmy, Desventri (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2019)
This article aims to explore a possible criterion of digital technology mathematics teachers’ professional development[1]. The criterion was canvassed through qualitative exploratory study which involve a hybrid model of DigiTech TPD, online published articles of related TPD, and theoretical perspective which relate to digital technology in mathematics education. Related frameworks (Drijverset al, 2010; Trocki Hollebrands, 2018) and content analysis were utilized to analyze the first two data. Theoretical perspectives of digital technology in mathematics education were accounted to reflect prior data and explore the criterion. We found that the current TPD[2]has not developed the knowledge of task design and supported teachers' roles in orchestrating technology-rich mathematics teaching as seen in the low level of tasks and teachers' orchestration in the classroom. Related articles on TPD in Indonesia show that the programs have not touched decisive factors of successfully implementing digital technology. An alternative criterion for DigiTech TPD is explored which includes three aspects namely theoretical approach, model and content. It could be alternative point of departure for designing and conducting DigiTech TPD in Indonesia.